2017
DOI: 10.1016/j.jebo.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control and performance appraisal

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 86 publications
(41 reference statements)
4
58
1
1
Order By: Relevance
“…Previous literature on public versus private sector employment considers specific personality traits (beyond the Big Five), such as locus of control, trust and reciprocity (Brewer, 2003;Dohmen and Falk, 2010;Dur and Zoutenbier, 2014;Heywood et al, 2017). Therefore we perform a third robustness check where we include locus of control, trust, positive reciprocity and negative reciprocity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature on public versus private sector employment considers specific personality traits (beyond the Big Five), such as locus of control, trust and reciprocity (Brewer, 2003;Dohmen and Falk, 2010;Dur and Zoutenbier, 2014;Heywood et al, 2017). Therefore we perform a third robustness check where we include locus of control, trust, positive reciprocity and negative reciprocity.…”
Section: Methodsmentioning
confidence: 99%
“…While motives reflect what people want to do or to have in the future (McClelland, ; Roberts, ), personality traits reflect general tendencies of thinking, feeling and acting (Roberts, , p. 140). The Big Five personality traits as a common model of personality, which include openness, conscientiousness, extraversion, agreeableness and neuroticism (Costa and McCrae, ), have been shown to be relevant for sector choice (Dohmen and Falk, ; Heywood et al ., ). We note that personality traits are not entirely distinct from motives, which becomes evident in the fact that the motive of laziness is – in inverted form – part of the personality trait conscientiousness in the SOEP measure (Gerlitz and Schupp, ; Hahn et al ., ).…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 97%
“…Additionally, as stated by Heckman (2011, p. 31), policy makers would gain a new 'avenue for intervention and policy' as the psychological impact of unemployment has been underestimated so far. Gathering specific insights on LOC's stability after job-loss, during unemployment 1 Additionally, studies have found an significant effect of LOC on entrepreneurial activity (Hansemark, 2003;Caliendo et al, 2014), occupational attainment and advancement (Andrisani, 1977;Cobb-Clark and Tan, 2011;Ahn, 2015;Schnitzlein and Stephani, 2016), maternity leave (Berger and Haywood, 2016), internal migration (Caliendo et al, 2015a), health behavior (Cobb-Clark et al, 2014), parental investment (Lekfuangfu et al, 2017), unemployment duration (Uhlendorff, 2004), selection into performance appraisal (Heywood et al, 2017), job satisfaction (Ng et al, 2006) and employment-related training (Caliendo et al, 2016). See Cobb-Clark (2015) for a comprehensive overview on LOC and labor market outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Performance appraisals may not only be used in allocating financial rewards, but also in providing feedback to workers, in making job assignment and in determining training needs (Heywood et al . ). Thus, performance appraisal use does not perfectly overlap with the use of performance pay.…”
Section: Data and Variablesmentioning
confidence: 97%
“…; Curme and Stefanec ; Dohmen and Falk ; Heywood et al . ). This research has used employee data to show that the self‐sorting into performance pay jobs can take place along multiple dimensions of the employees’ personal characteristics.…”
Section: Introductionmentioning
confidence: 97%